Expression and identification of a laminin-binding protein in Aspergillus fumigatus conidia. - Tronchin, G (1997)
Adhesion of Aspergillus fumigatus, the causative agent of human aspergillosis, to the extracellular matrix protein laminin has been previously demonstrated. This study investigated the expression of laminin receptors during swelling of conidia, a step leading to germination and subsequent colonization of tissues. Scanning electron microscopy showed that the laminin binding sites were distributed over the external rodlet layer of resting conidia. During swelling, the characteristic rodlet layer progressively disintegrated and conidia surrounded by a smooth cell wall layer appeared. Flow cytometry using fluorescein isothiocyanate-conjugated laminin demonstrated that expression of laminin receptors at the surface of conidia was swelling dependent. Resting conidia expressed high levels of laminin receptors on their surface. A gradual decrease of laminin binding was then observed as swelling occurred, reaching a minimum for 4-h-swollen conidia. This correlated with a loss of adherence of swollen conidia to laminin immobilized on microtiter plates. Trypsin pretreatment of conidia reduced laminin binding. Analysis by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and ligand blotting with laminin identified in a cell wall extract a major 72-kDa cell wall glycoprotein which binds laminin. Thus, one of the initial events in the host colonization may be the recognition of basement membrane laminin by this 72-kDa cell wall surface component.